Focus : Les archives audiovisuelles de la justice - Martine Sin Blima-Barru (Criminocorpus)
The singularity of the recordings made in the Justice Ministry’s audio-visual archives gives them a special place in the French Heritage Code compared with other archives. Its history and legal status explain its specific features. Thanks to the Law of the 11th of July 1985 as advocated by then Minister of Justice, Robert Badinter, cameras have been allowed into courtrooms, to constitute the memory of the Judiciary through historical video or sound archives, in their entirety, without cuts, additions or editing.This new law broke the ban on filming or photographing trials, which dated back to 1954. Since then, 28 trials have been recorded: crimes committed during the Second World War, crimes against humanity, crimes of genocide against the Tutsi in Rwanda, crimes of terrorist attacks. The historical subjects characterise their recording. Accessing and consulting these archives is a social, educational and remembrance issue.